Improving Vocabulary through the Ome Tv Application - Khoiro, Audia Haditsa; Hafidzah, Azkiya Dzuriyati; Fazrin, Herawati; Nurrohman, Lucky; Khomarudin, Khomarudin (LINGUAMEDIA Journal, 2024)
This study examines the effectiveness of the Ome TV application in improving English vocabulary and pronunciation for non-native speakers. The study uses a qualitative descriptive approach and content analysis to analyze the impact of Ome TV on language learning. Previous studies have shown that Ome TV can improve speaking skills, vocabulary, and pronunciation for non-native speakers. The study uses a qualitative descriptive approach and content analysis to analyze the impact of Ome TV on language learning. Previous studies have shown that Ome TV can improve speaking skills, pronunciation, vocabulary, and self-confidence, as well as courage. The content analysis of the conversations between the participants and native English speakers revealed that the participants were able to use more complex vocabulary and sentence structures after using Ome TV. The results of this study suggest that Ome TV is an effective tool for improving English language skills, as it provides opportunities for users to interact with native English speakers and expand their vocabulary. Additionally, using Ome TV can increase users' confidence and willingness to communicate in English. Overall, this study highlights the potential of Ome TV as a language learning tool for non-native speakers.